2019
DOI: 10.1653/024.102.0139
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Liriomyza huidobrensis (Diptera: Agromyzidae) Disseminating Alternaria solani (Pleosporaceae) in Potato Crops in Brazil

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…A high correlation between L. huidobrensis and early blight caused by A. solani (Soares et al, 2019), where leaf miner and the incidence of Alternaria leaf blight lesions were observed on muskmelon plants (Chandler and Thomas, 1991). Also, our results are similar to the obtained results by Soares et al, (2019), who reported a high correlation between the number of L. huidobrensis mines and A. solani spots and the dissemination of A. solani in potato plants. In addition to the previously reported roles of leaf miner adults and the number of mines in the occurrence of early blight, our results showed a high correlation between the number of larvae and minded area as both facilitate the infection by A. solani and other unstudied diseases.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A high correlation between L. huidobrensis and early blight caused by A. solani (Soares et al, 2019), where leaf miner and the incidence of Alternaria leaf blight lesions were observed on muskmelon plants (Chandler and Thomas, 1991). Also, our results are similar to the obtained results by Soares et al, (2019), who reported a high correlation between the number of L. huidobrensis mines and A. solani spots and the dissemination of A. solani in potato plants. In addition to the previously reported roles of leaf miner adults and the number of mines in the occurrence of early blight, our results showed a high correlation between the number of larvae and minded area as both facilitate the infection by A. solani and other unstudied diseases.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies confirmed the correlation between leaf miner infestation and plant disease development (Munkvold et al, 1996;Ahmed et al, 2001 andDeadman et al, 2002). A high correlation between L. huidobrensis and early blight caused by A. solani (Soares et al, 2019), where leaf miner and the incidence of Alternaria leaf blight lesions were observed on muskmelon plants (Chandler and Thomas, 1991). Also, our results are similar to the obtained results by Soares et al, (2019), who reported a high correlation between the number of L. huidobrensis mines and A. solani spots and the dissemination of A. solani in potato plants.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations